Scribes and translators : Septuagint and Old Latin in the Books of Kings - Fernandez Marcos, Natalio, 1940- (Vetus Testamentum, Supplements, 1994)
Scribes and Translators is a critical reflection on the textual pluralism as reflected in the book of Kings. The first part of the book examines the diverse texts transmitted by the manuscripts. Special attention is paid to the Antiochene text of the Septuagint that is being edited in Madrid. The second part is devoted to the analysis of Old Latin readings, transmitted by a Spanish family of Vulgate Bibles, with no support in any of the known manuscripts. Finally, the whole evidence is discussed in the frame of the plurality of texts confirmed by the Qumran documents for those books. Based on Old Latin material recently published it sheds light on the text transmission of Kings and on the translation techniques and the history of the Biblical texts in general.